Killer whales (Orcinus orca) hunt, kill and consume the largest fish on Earth, the whale shark (Rhincodon typus) - Francesca Pancaldi; Kathryn A. Ayres; Austin J. Gallagher; James Moskito; Kelsey C. Williamson; Jesús Erick Higuera Rivas; Jesús Erick Higuera Rivas (Frontiers in Marine Science)
Killer whales (Orcinus orca) are the apex predator in global oceans, and as such they are afforded access to prey species at all trophic levels and sizes. Due to their enhanced cognitive abilities, they are frequent predators of other ocean giants, including large sharks. Observations of these predator-prey interactions are rare globally; however, records appear to be increasing in recent years, possibly due to increased access to surveillance. Here we present reports of killer whales hunting and preying on the world’s largest fish species, the whale shark (Rhincodon typus), by collating and analyzing photo and video footage collected from four unique predation events spanning six years (2018 – 2024) in the southern Gulf of California. Across all events, orcas displayed a seemingly approach to collaboratively hunting and killing whale sharks, characterized by focusing on attacking the pelvic area (claspers and pelvic fins) which exsanguinates the prey and allows access to the lipid-rich liver. Photo identification of the killer whales revealed that an individual adult male “Moctezuma” was engaged in three of the four events, and the females involved in event four had previously been sighted with him. We suggest the potential existence of a specialized pod of elasmobranch-hunting killer whales occurring in the Gulf of California.